Bermain sambil belajar: Strategi Pembelajaran Kreatif di Pendidikan Anak Usia Dini ramah anak - Limbong, Christin Yekesinta; Sindi Rotua Pardede; Dahlia Padang; Etri Rehenda (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research explores creative learning strategies that can be applied in Early Childhood Education (ECE) to facilitate fun and meaningful learning experiences for children. Through a play while learning approach, the main goal of this research is to create a child-friendly learning environment where children can develop their cognitive, motor, social and emotional skills. This research method involves a literature review from various sources that discusses the concept of playing while learning, creative learning strategies, and appropriate approaches for ECE. The results of this literature review are then used to formulate concrete strategies that can be applied in the ECE context. Some of the creative strategies identified include thematic learning, role playing, creative play using various types of materials, sensory activities, collaborative learning, use of the environment, and appropriate use of technology. These strategies aim to increase children's involvement in the learning process, stimulate their imagination and creativity, and strengthen their understanding of various concepts and skills. The practical implication of this research is the importance of developing a curriculum and learning approach that takes into account children's needs and interests, and provides space for them to explore and learn through direct experience. By implementing this creative learning strategy, it is hoped that ECE can become a fun and stimulating environment for children to grow and develop holistically.